(3cJGH aj GdfMhs ((3CHf eMeO GdUZjQ s)
(3ChdgG (B:s
(3bGd GdTjN QMeg Gddg GdcdGe YfO GdfMGI ebjO HCQHYI bjhO GdChd GddaX hgh s
(3BNQgG (B:s
(3fMh ZdGe RjO, hcJGH YeQ, jYfj ZdGe dRjO hcJGH dYeQh hMOg BNQ GdcdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B261 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs